Gender and Diversity Studies European Perspectives - Jungwirth, Ingrid; Bauschke-Urban, Carola (Verlag Barbara Budrich, 2019)
What concepts of 'gender' and 'diversity' emerge in the different regions and pertinent research and practical fields? On the back drop of current European developments - from the deregulation of economy, a shrinking welfare state to the dissolution and reinforcement of borders - the book examines the development of Gender and Diversity Studies in different European regions as well as beyond and focuses on central fields of theoretical reflection, empirical research and practical implementation policies and politics.